Ultrasound image of healthy skin in newborns in the first 24 hours of life - Przybysz Paulina; Jackowska Teresa; Wilińska Maria; Malinowska Sylwia; Wójtowicz Joanna; Mlosek Robert Krzysztof (Journal of Ultrasonography, 2020)
Introduction: Ultrasound imaging is a safe, repeatable and easily available imaging procedure. Based on these qualities, it may become a useful tool for skin assessment in newborns. Aims: The aim of the study was to evaluate the usefulness of high-frequency ultrasound imaging for neonatal skin assessment. Another aim was to identify differences in ultrasound features of the skin in newborns depending on the examination site, sex, age, birth weight, and arterial blood gas results. Material and method: A total of 72 newborns in the first 24 hours of life, without any skin lesions, were included in the study. All newborns underwent ultrasound skin examinations in three body sites (forearm, abdomen and thigh) during the first 24 hours of life. DermaMed Ultrasound Scanner with a 48 MHz probe was used for imaging. A total of three structures were identified in the ultrasound images: epidermal echo, dermis, and subcutaneous tissue. The study assessed the thickness of the epidermis and dermis, and the echogenicity of the dermis and subcutaneous tissue. Data were analysed to determine possible links with sex, post-conceptional age, body weight, birth route, and results of umbilical cord blood gas analysis. Results: Depending on the body site examined, the mean epidermal thickness was 0.081 to 0.083 mm, while the mean thickness of the dermis ranged between 0.679 and 0.722 mm. The newborns with higher birth weights were shown to have a thicker epidermis regardless of the examined site [R (correlation coefficient) for the forearm: 0.47 (p <0.001), abdomen: 0.53 (p <0.001), thigh: 0.48 (p <0.001)]. A positive correlation was found between epidermal and dermal thickness (R = 0.34; p = 0.004), but a comparison of the three examined sites revealed no significant differences in the thickness of the two structures. The sex of the newborn had no significant effect on the ultrasound features of the skin. None of the ultrasound parameters under study was found to correlate with the pH level in umbilical cord blood gas analysis. Subcutaneous oedema was detected in the examined sites in all the newborns studied. Conclusions: High-frequency ultrasound imaging may become a useful method for neonatal skin assessment, complementing existing diagnostic techniques for monitoring pathologically altered skin.